Improved strength and ductility of friction stir tailor-welded blanks of base metal AA2024 reinforced with interlayer strip of AA7075 - Sadoun, A.M.; Meselhy, A.F.; Deabs, A.W. (Results in physics, 2020)
•FSW technique with compensation interlayer was applied to tailor-weld aluminum blanks.•With the aim of improving welded joint strength and ductility.•The optimum compensation interlayer width is 2 mm strength is improved by 18%.•The failure strain is improved by 54% compared to without compensation interlayer.•The improved strength caused by precipitation of Al2Cu and Mg2Zn intermetallic phases. Most of welded parts requires secondary forming process to meet the design requirements which makes the ductility of the joint an important parameter to be improved. To this end, we imped compensation layer of AA7075 aluminum alloy between two blanks of AA2024 aluminum alloy during friction stir welding. The effect of compensation layer width on the microstructure, microhardness, tensile strength and failure strain was investigated. XRD results showed that using AA7075 alloy compensation layer helped for precipitation of new intermetallic phases, Al2Cu and Mg2Zn, at the grain boundaries of Al grains. Tensile test results showed that the sample with 2 mm width compensation layer possess 18% improved strength and 54.4% improved failure strain compared with the joint without compensation layer. The failure strain of this joint was 16.8% which is almost that for AA2024 (17.2%). The improved strength was because of the grain refinement and the precipitation of Al2Cu and Mg2Zn intermetallics. While the improved failure strain was due to the higher content of Mg and Zn alloying elements in AA7075 alloy which precipitate on the grain boundaries facilitating the slipping between grains and provide more deformability of the global structure.